Itikad Baik Konsumen Dalam Pemanfaatan Air Bersih - Usmany, Dominggus Pier; Kuahaty, Sarah Selfina; Pesulima, Theresia Louize (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Some of the findings of cases carried out by the Regional Drinking Water Company of Ambon City, in fact, consumers as customers do not use clean water in accordance with the Consumer Protection Law which regulates consumer obligations, especially consumers' good ethics towards companies.Purposes of the Research: To find out the form of consumer good faith in the use of clean water and legal remedies that can be taken by business actors against consumers who do not have good intentions in the use of clean water.Methods of the Research: The method used is normative legal research. The research approach is a statutory approach and a conceptual approach. Sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The technique of collecting legal materials is through literature study and then analyzed through a perspective using qualitative methods.Results of the Research: The results of the study indicate that consumers/customers are obliged to carry out their obligations to the Regional Drinking Water Company of Ambon City. Legal Efforts to resolve disputes, broadly speaking, there are two models of civil dispute resolution, namely litigation and non-litigation. These two types of dispute resolution models are anticipated when a dispute cannot be resolved with only one settlement model. Consumers who have obtained their rights from the Regional Drinking Water Company of Ambon City/business actors but they do not have the good faith to carry out their obligations may be subject to sanctions.